Multigravida dengan Vertigo - Adhi putri, Citra; Shariff, Fonda Octarianingsih (CV. Jasa Sukses Abadi, 2025)
Pregnancy causes significant hormonal changes, particularly increased estrogen and progesterone, which can affect the audiovestibular system. This condition is associated with the onset of vertigo, balance disorders, and even temporary hearing loss. The physiological state of pregnancy in women is quite significant due to the impact of hormones, the cardiovascular system, and psychological changes. The circulatory, respiratory, gastrointestinal, musculoskeletal, dermatological, and auditory vestibular systems all undergo structural and functional changes as a result of certain hormones such as progesterone, estrogen, placental lactogen, and human chorionic gonadotropin. The audiovestibular system is involved in several symptoms, including hearing loss, tinnitus, facial nerve paralysis, otosclerosis, autophony, and vertigo, which may appear for the first time or worsen during pregnancy. This case reports a 27-year-old woman, G5P1A3, at 17 weeks of gestation, presenting with complaints of spinning dizziness, vomiting, weakness, and epigastric pain. Anamnesis, physical examination, hematological tests, and obstetric ultrasonography were performed. The diagnosis revealed a multigravida with vertigo, with differential diagnoses of vertigo, cephalgia, and hyperemesis gravidarum. The patient received intravenous fluids (Ringer’s Lactate), ondansetron, vitamin B6, dimenhydrinate, and paracetamol. Vertigo in pregnancy is a frequent and disturbing condition, characterized by a spinning sensation, dizziness, and instability or unsteadiness. These symptoms result from hormonal changes during pregnancy that affect the audiovestibular system and may worsen in subsequent trimesters. Vertigo in pregnancy is a multifactorial condition related to both physiological and hormonal changes, with diagnosis established through anamnesis, physical examination, and supporting investigations.